Rapid Pharmacokinetic and Biodistribution Studies Using Cholorotoxin-Conjugated Iron Oxide Nanoparticles: A Novel Non-Radioactive Method - Lee, Michelle Jeung-Eun; Veiseh, Omid; Bhattarai, Narayan; Sun, Conroy; Hansen, Stacey J.; Ditzler, Sally; Knoblaugh, Sue; Lee, Donghoon; Ellenbogen, Richard; Zhang, Miqin; Olson, James M. (PLOS ONE, 2010)
Background Recent advances in nanotechnology have led to the development of biocompatible nanoparticles for in vivo molecular imaging and targeted therapy. Many nanoparticles have undesirable tissue distribution or unacceptably low serum half-lives. Pharmacokinetic (PK) and biodistribution studies can help inform decisions determining particle size, coatings, or other features early in nanoparticle development. Unfortunately, these studies are rarely done in a timely fashion because many nanotechnology labs lack the resources and expertise to synthesize radioactive nanoparticles and evaluate them in mice. Methodology/Principal Findings To address this problem, we developed an economical, radioactivity-free method for assessing serum half-life and tissue distribution of nanoparticles in mice. Iron oxide nanoparticles coated with chitosan and polyethylene glycol that utilize chlorotoxin as a targeting molecule have a serum half-life of 7–8 hours and the particles remain stable for extended periods of time in physiologic fluids and in vivo. Nanoparticles preferentially distribute to spleen and liver, presumably due to reticuloendothelial uptake. Other organs have very low levels of nanoparticles, which is ideal for imaging most cancers in the future. No acute toxicity was attributed to the nanoparticles. Conclusions/Significance We report here a simple near-infrared fluorescence based methodology to assess PK properties of nanoparticles in order to integrate pharmacokinetic data into early nanoparticle design and synthesis. The nanoparticles tested demonstrate properties that are excellent for future clinical imaging strategies and potentially suitable for targeted therapy.